Bronchopulmonary dysplasia: what are its links to COPD?. (December 2019) - McGrath-Morrow, Sharon A.; Collaco, Joseph M.
Emerging evidence suggests that adverse early life events can affect long-term health trajectories throughout life. Preterm birth, in particular, is a significant early life event that affects approximately 10% of live births. Worldwide, prematurity is the number one cause of death in children less than 5 years of age and has been shown to disrupt normal lung development with lasting effects into adult life. Along with impaired lung development, interventions used to support gas exchange and other sequelae of prematurity can lead to the development of bronchopulmonary dysplasia (BPD). BPD is a chronic respiratory disease of infancy characterized by alveolar simplification, small airways disease, and pulmonary vascular changes. Although many survivors of BPD improve with age, survivors of BPD often have chronic lung disease characterized by airflow obstruction and intermittent pulmonary exacerbations. Long-term lung function trajectories as measured by FEV1 can be lower in children and adults with a history BPD. In this review, we discuss the epidemiology and manifestations of BPD and its long-term consequences throughout childhood and into adulthood. Available evidence suggests that disrupted lung development, genetic susceptibility and subsequent environment and infectious events that occur in prenatal and postnatal life likely increase the predisposition of children with BPD to develop early onset chronic obstructive pulmonary disease (COPD). The reviews of this paper are available via the supplemental material section.